Pengaruh Berbagai Jenis Zat Pengatur Tumbuh dan Asal Stek Batang Terhadap Pertumbuhan Vegetatif Bibit Tanaman Tapak Dara (Catharanthus roseus (L.) G. Don) - Siti Nurhaeni; Muharam; Hayatul Rahmi (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2020)
This research was purposed to study The effect of Various Plant Growth Regulator and origin of stem cutting on vegetative Growth of Periwinkle (Catharanthus roseus (L.) G. Don). The experiment was conduced in Cengkong village Purwasari District of Karawang from April until June 2020.This research used Randomized Block Desain (RBD) factorial pattern 3 x 3 and repeated 4 times. First factor is the type plant growth regulator (Z) consist of three levels, namely; z0 = water, z1 = 100% coconut water extract, and z2 = Rootone-F 100 ppm. Second factor is origin of stem cutting (B) consist of three levels, namely: b1 = base of stem, b2= middle stem, and b3 = upper stem.The result of this reseach showed no interaction between the type plant growth regulation and stem origin on vegetative growth of periwinkle plant. However there are, the origin of upper stem has the best effect to the presentation of stem life, stem height, amount of leaves, roots length, amount of root, and growing speed of stem. Whereas, the middle stems has the best effect of the shoots appear and amount of shoots.